Docetaxel, Oxaliplatin, and 5‐Fluorouracil (DOF) in Metastatic and Unresectable Gastric/Gastroesophageal Junction Adenocarcinoma: A Phase II Study with Long‐Term Follow‐Up. (28th May 2019) - Rosenberg, Ari Joseph; Rademaker, Alfred; Hochster, Howard S.; Ryan, Theresa; Hensing, Thomas; Shankaran, Veena; Baddi, Lisa; Mahalingam, Devalingam; Mulcahy, Mary F.; Benson, Al B.
Abstract: Lessons Learned: Adding docetaxel to the modified FOLFOX7 backbone (DOF) is a feasible three‐drug combination therapy for advanced gastric cancer with high activity, providing evidence that leucovorin is not necessary in this setting. The DOF regimen represents an alternative to the FLOT (5‐FU 2, 600 mg/m 2 as 24‐hour infusion with leucovorin 200 mg/m 2, oxaliplatin 85 mg/m 2, and docetaxel 50 mg/m 2 ) regimen that can be considered in select patients with advanced gastric cancer and is a potential choice in the curative setting. Background: The combination of docetaxel, cisplatin, and 5‐fluorouracil (5‐FU) demonstrates high response rates in advanced gastric cancer, albeit with increased toxicity. Given the efficacy of platinum‐taxane‐fluoropyrimidine regimens, this phase II study evaluated the efficacy and toxicity of docetaxel, oxaliplatin, and 5‐FU (DOF) for the treatment of metastatic or unresectable gastric or gastroesophageal junction (GEJ) adenocarcinoma. Methods: Patients with metastatic or unresectable gastric or GEJ adenocarcinoma with no prior therapy for metastatic disease received docetaxel 50 mg/m 2 on day 1, oxaliplatin 85 mg/m 2 on day 1, and 5‐FU 2, 400 mg/m 2 continuous intravenous infusion over 46 hours; cycles were repeated every 2 weeks. The primary endpoint was overall response rate (ORR). Results: Forty‐four patients were enrolled. Assessment of treatment response and toxicity was feasible in 41 and 43 patients, respectively. ORR was 73.2% (68.3% partial response; 4.9% complete response). Therapy was discontinued for progressive disease in 53%, toxicity in 26%, and death on treatment in 16%. Two patients underwent surgical resection. Thirty‐three patients (76.7%) received at least seven cycles (7–34). Grade 3–4 toxicities occurred in 31 patients (72.1%), including neutropenia (23.3%), neurologic (20.9%), and diarrhea (14.0%). Median overall survival was 10.3 months. Conclusion: DOF demonstrates a high response rate, expected safety profile, and prolonged survival and remains an option for select patients with unresectable or metastatic gastric or GEJ adenocarcinoma.